The Language Letters : Selected 1970s Correspondence of Bruce Andrews, Charles Bernstein, and Ron Silliman - Golston, Michael; Hofer, Matthew (Book collections on Project MUSE., 2019)
Written between 1970 and 1978, these letters detail the development of the concepts and styles that came to define one of the most influential movements in post-1960s writing.